Sepulturas escavadas na rocha no curso inferior da bacia do Rio Lima [recurso eletrónico] : o Concelho de Viana do Castelo em perspetiva - Arezes, Andreia (2021)
Rock-cut graves are particular forms of expression of medieval communities in their response to death. Endowed with morphological specificities whose evolution and chronology have long been sought to outline, they mark the landscape and materialize aspects of the underlying religious and socioeconomic sensitivities. In this text I approach the rock-cut graves detected in the downstream sector of the Lima basin, a territory that, from an administrative point of view, is largely correspondent to the current municipality of Viana do Castelo, located in the western façade of the northwest of Iberian Peninsula. Using researches and inventories previously carried out as a starting point I propose, on the one hand, to return to a set of sites that have been already listed and described, in order to revisit the reported occurrences and the current state of conservation of the structures. On the other hand, to confront different published data with renewed observations, aiming to validate and to complement the mapping of this type of funerary manifestation, transversal to different European geographies, although with special representation in the Iberian Peninsula.